Perbandingan Tingkat Keparahan Infeksi Primer Virus Dengue Serotipe 1, 2, 3 dan 4 di Indonesia: Systematic Review - Mardhatillah Sariyanti; Nur Fitri; Ety Febrianti; Annelin Kurniati; Debie Rizqoh (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Dengue virus infection (DENV) circulates in various hyperendemic and endemic areas that has increase mortality year by year. Indonesia is the second-largest country which is endemic to dengue infection between 30 other countries in the world. There are four circulating dengue virus (DENV) serotypes, namely DENV-1, DENV-2, DENV-3, and DENV-4. Each serotype shows a different clinical manifestation and severity. This systematic review aims to compare the severity of dengue virus primary infection and serotype 1,2,3,and 4. Data were collected based on studies of the severity of primary infections caused by various DENV serotypes in Indonesia. Data was searched using a database in the form of Pubmed and Chocrane. The keywords used are (Primary dengue infection OR dengue primary infection) AND (serotype OR serogroup OR serotype dengue)) AND (severity OR severe dengue* OR severity of illness index* OR clinical manifestations OR clinical features OR clinical characteristics) AND Indonesia. Based on search results, we obtained 7 studies out of 699 studies. 7 studies found that there are differences in serotype circulation in Indonesia. DENV-3 is dominant in 7 cities in Indonesia, while DENV-1 is dominant in Surabaya, Bali, and Jambi. Dengue fever shows a greater percentage than DHF / DSS. The proportion of severity is lower in primary infections.